2011
DOI: 10.1055/s-0031-1286292
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia and Exercise

Abstract: One of the most important objectives of intervention programs for persons with haemophilia (PWH) is to improve their quality of life. Regular physical activity has been recommended as an adjunct to conventional treatment, with positive results in the prevention of joint problems and bleeding, in addition to the improvement in cardiovascular function, muscle strength, and body composition. The objective of the present review was to present the benefits of aerobic and resistance training programs in PWH, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 21 publications
1
67
0
Order By: Relevance
“…Seven reviews reported data regarding disease severity 6,8,[21][22][23][24]28 ; In three of them, no data related to the age range of the participants were reported.…”
Section: Populationmentioning
confidence: 99%
“…Seven reviews reported data regarding disease severity 6,8,[21][22][23][24]28 ; In three of them, no data related to the age range of the participants were reported.…”
Section: Populationmentioning
confidence: 99%
“…Patients with haemophilia are advised to avoid high impact contact sports such as rugby,2 although physical exercise is known to be of benefit to their general health, bone density and joint stability 3 4. The role of police officer is confrontational, physical and analogous to a contact sport.…”
Section: Discussionmentioning
confidence: 99%
“…66,67 This is especially important for teens and young adults. 66,67 This is especially important for teens and young adults.…”
Section: General Considerations Throughout the Lifespanmentioning
confidence: 99%